2011
DOI: 10.1021/ie1014348
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids as Raw Material for Biocompatible Surfactants

Abstract: Surfactants are chemical products consumed in large quantities every day on a worldwide scale. The development of less irritant, less toxic, consumer-friendly surfactants is, therefore, of general interest. Amino-acid-based surfactants constitute a novel class of surfactants produced from renewable raw materials and can be seen as an alternative to conventional surfactants. With the aim of testing their applicability in formulations for pharmaceutical, food, and cosmetic industries we have carried out exhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 83 publications
0
100
0
Order By: Relevance
“…The SPP values calculated for Bz-Arg-NHC 10 and Bz-Arg-NHC 12 were 0.38 and 0.45 respectively, thus predicting the formation of cylindrical micelles with both lipoamino acids. Pinazo et al 13 reported the aggregation of N a -acyl-arginine methyl ester into classical spherical micelles. In this instance, the prediction based on the estimated SPP value (SPP ¼ 0.31) was conrmed by NMR, light scattering, and small-angle-X-ray-diffraction scattering.…”
mentioning
confidence: 99%
“…The SPP values calculated for Bz-Arg-NHC 10 and Bz-Arg-NHC 12 were 0.38 and 0.45 respectively, thus predicting the formation of cylindrical micelles with both lipoamino acids. Pinazo et al 13 reported the aggregation of N a -acyl-arginine methyl ester into classical spherical micelles. In this instance, the prediction based on the estimated SPP value (SPP ¼ 0.31) was conrmed by NMR, light scattering, and small-angle-X-ray-diffraction scattering.…”
mentioning
confidence: 99%
“…The long aliphatic chain can be bound to the amino acid by acyl, ester,a lkyl or amide linkages and their synthesis is based on organic or enzymatic processes [133]. Amino acid-based surfactants are classified based on three main structures: linear or as ingle chain, dimeric or gemini and glycerolipid-like structures; depending on the choice of amino acid and the synthesis procedure, either anionic, cationic, non-ionic or amphoteric surfactants can be prepared [14].…”
Section: Amino Acid As Polar Headgroupmentioning
confidence: 99%
“…Cytotoxicity of the amino acid-based surfactants is dependent on structure of the surfactant of head group or hydrophobic group or size of the counter ion 3,40 . Based on in vitro and in vivo studies, amino acid-based surfactants may offer use in pharmaceutical, skin care and cosmetic applications due to their lower irritancy potential, less toxic and high biodegradability 41,42 .…”
Section: In Vitro Cytotoxicity Assessmentmentioning
confidence: 99%